(untitled) (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Tóm tắt: Sử dụng các phương pháp nghiên cứu khoa học phổ biến trong lĩnh vực TDTT, các tác giả đã lựa chọn được 25 tiêu chí thuộc 5 nhóm đánh giá thực trạng hoạt động sự kiện thể thao tại vùng Trung du và miền núi Bắc Bộ, trên cơ sở đó, tiến hành đánh giá thực trạng. Kết quả cho thấy: có 40% các tiêu chí được đánh giá ở mức độ khá, các tiêu chí còn lại đều được đánh giá ở mức trung bình, cận khá.. Từ khóa: Thực trạng, hoạt động sự kiện thể thao, vùng Trung du và miền núi Bắc Bộ. Assessing the current status of sports event activities in the Northern Midlands and Mountains region Summary: Using popular scientific research methods in the field of physical education and sports, 25 criteria belonging to 5 groups of criteria were selected to evaluate the current status of sports event activities in the Northern midlands and mountainous regions, on that basis. , conduct an assessment of the current situation. The results show that: 40% of the criteria are rated at a good level, the remaining criteria are all rated at an average or near-good level. . Keywords: Current status, sports event activities, sports events, Northern Midlands and Mountains region.